Management of fully edentulous with flabby ridge using double spacer custom tray and modified impression techniques - Sara Stefany; Taufik Sumarsongko; Rasmi Rikmasari (Indonesia Prosthodontic Association, 2026)
Background: A flabby ridge refers to an area of alveolar ridge with hypermobile and fibrous soft tissue that typically forms as a result of prolonged pressure or unstable occlusion, which posing difficulties in achieving proper denture retention, support, and stability. A precise impression is essential for ensuring the stability of complete dentures with flabby ridge. The fundamental principle for impressions of a flabby ridges is to apply minimal pressure on the flabby area to prevent distortion impression outcome. To achieve that, double spacer custom tray along with selective pressure impression techniques was employed. Objectives: This case report aims to gain impression with minimum pressure on flabby ridge to enhance retention, support, and stability of the complete denture. Case Report: A 70-year-old male patient came to the Policlinic Prosthodontics Oral dan Dental Hospital Universitas Padjadjaran complaining that his old 10-years-used denture felt loose and uncomfortable. Intraoral examination showed that both maxillary and mandibular arches were fully edentulous, with flabby ridges present. Following the assessment, it was decided to make a new complete denture using double spacer custom tray and selective pressure impression techniques. Conclusion: Double spacer custom tray and selective pressure impression techniques have been effective in minimizing pressure that could lead to tissue compression during impression procedures, resulting more comfortable dentures with greater retention and stability. Keywords: Flabby Ridge, Complete Denture, Double Spacer Custom Tray, Selective Pressure Impression Technique